Pengaruh Literasi Keuangan, Inklusi Keuangan, Dan Teman Sebaya Terhadap Perilaku Menabung Melalui Self Control Sebagai Variabel Intervening Pada Mahasiswa Fakultas Ekonomi Perguruan Tinggi Negeri Di Surabaya - Erna Delina Siboro; Rochmawati . (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
This research is conducted with the aim of analyzing the influence of financial literacy, financial inclusion, and peers on saving behavior through self-control as intervening variables in 920 students of the Faculty of Economics at State Universities in Surabaya. The sample of this research amounted to 211 sample taken with random sampling techniques. Data collection techniques using tests and questionnaires, which are analyzed by the SPSS 25 program. The results showed: 1) financial literacy has a negative and significant effect of 0,038 on saving behavior, 2) financial inclusion has an influence and significance of 0,001 on saving behavior, 3) peers has an influence and significance of 0,018 on saving behavior, 4) self-control has an influence and significance of 0,000 on saving behavior, 5) financial literacy has no significant effect 0,131 on saving behavior through self-control, 6) financial inclusion has a significant effect of 0,013 on saving behavior through self-control, 7) peers has a significant influence 0,012 on saving behavior through self-control.